Pengaruh Orientasi Pasar pada Kinerja Perusahaan Kecil - Susanto, Perengki (Jurnal Kajian Manajemen Bisnis, 2012)
Previous studies on market orientation emphasizes on the performance of medium or large enterprises. These findings can not be generalized in the context small firms due to differences in the phenomena that affect the behavior or competitive action, speed of response to the threat and business opportunity (Chen & Hambrick, 1995). In addition, some have argued consistently that small and large companies require different strategies for success in the industry (Hambrick et al., 1982; Woo & Cooper, 1981, 1982). Therefore, this study aimed to determine the effect of market orientation on the performance of small firms. The respondents were managers or owners of small enterprises in Yogyakarta. Sampling was done by purposive sampling method. Sample size was 105 small enterprises in Yogyakarta. Methods of analysis used is multiple regression analysis. The results showed that customer orientation has positive and significant effect on the performance; competitor orientation has negative and significant effect on the performance, and coordination inter-function has positive and no significant effect on the performance of small firms.